Detection of apoptosis by the TUNEL technique in clinically localised prostatic cancer before and after combined endocrine therapy. Issue 5 (May 1997) - Colecchia, M; Frigo, B; Del Boca, C; Guardamagna, A; Zucchi, A; Colloi, D; Leopardi, O
Abstract : AIMS: Apoptosis in prostate cancer was evaluated after three months of combined endocrine therapy to investigate the association with tumour grade, tumour stage, and the immunohistochemical detection of p53 and bcl-2 in tumour cells before and after therapy. METHODS: Twenty six formalin fixed, paraffin wax embedded core biopsies and corresponding prostatectomy specimens, excised after three months of combined endocrine therapy, were analysed for the presence of apoptotic cells by the terminal deoxynucleotidyl transferase mediated dUTP-biotin nick end labelling (TUNEL) method, and for p53 and bcl-2 overexpression by immunohistochemistry. RESULTS: All 26 adenocarcinomas were clinically localised at diagnosis. In biopsies performed before combined endocrine therapy, the apoptotic indices varied between 0.09% and 1.73%, while the tumour grade fell between Gleason score 1 and 8. The mean (SD) apoptotic count pretherapy was 0.71% (0.50). There was a significant association between elevated apoptotic counts and higher Gleason scores in the biopsies (p = 0.005). After three months of therapy, the percentage of apoptotic tumour cells increased independently of tumour stage, while a significant association with Gleason grade was found (p = 0.0018) and all the tumours had Gleason scores of < 7. In eight cases the apoptotic index was more than twice its pretherapy value. The remaining tumours showed less of an increase in the apoptotic index (five cases) or a reduction in the percentage of apoptotic cells. The overall moderate increase in apoptotic index after combined endocrine therapy was not statistically significant (p = 0.8). Immunoreactivity to p53 was absent in all cases, before and after therapy, while a slight increase in the number of cells overexpressing bcl-2 was observed in five of the 13 tumours (38.1%) with reduced apoptotic indices after therapy. CONCLUSIONS: After three months of combined endocrine treatment a minority of clinically localised prostate neoplasms showed regressive epithelial alterations, associated with an increase in apoptotic tumour cells; an increase in cells overexpressing bcl-2 was observed in five of the 13 tumours with reduced apoptotic indices.